Legal Politics in The Democratic State of Timor Leste - Baptista, Manuel João (Jurnal Sosial Teknologi, 2025)
This research aims to analyze the role of legal politics in Timor-Leste in building a strong democratic system, as well as the challenges faced in law enforcement and the harmonization of legal regulations post-independence. The method used is normative analysis with historical and conceptual approaches, where data is collected through literature review, legal regulations, and related official documents. The results show that despite various legal reforms, the legal system in Timor-Leste still faces significant challenges, such as the imbalance between existing regulations and social needs and the limited capacity of law enforcement that hinders the effectiveness of policies. Additionally, there is still a strong political influence in the legislative process, which often affects the independence of judicial institutions. The implications of this study emphasize the importance of enhancing the capacity of law enforcement agencies and the strong commitment of all parties to strengthen the effectiveness of legal policies to support the achievement of sustainable democracy and the rule of law in Timor-Leste. This study is expected to contribute to developing legal policies that are more responsive to the country's evolving social and political needs.